Neuropeptides and Behaviour: From Motivation to Psychopathology - Carol F. Elias (Frontiers Research Topics, 2017)
The discovery of the involvement of neuropeptides with behaviours other than regulatory motivated ones took place in the midst of 1960's with David de Wied's first report on the influence of pituitary peptides on memory. This major scientific breakthrough opened a new frontier of studies in Endocrinology and its related fields, Neuroendocrinology and Psychoneuroendocrinology. Neuropeptides were initially thought to be involved in homeostatic regulation and secreted only from neurons located in the hypothalamus; they are now recognized neurotransmitters, produced in and secreted from distinct brain areas, associated with a myriad of, not only, motivated, but also psychopathological behaviours. Motivated behaviours are determinant for individual and species survival, but their expression in a large spectrum and deviations from average may give rise to a number of psychiatric conditions.